Comparison of Primary and Secondary Prophylaxis Using PEGylated Recombinant Human Granulocyte–Stimulating Factor as a Cost-Effective Measure in Malignant Neoplasms: A Multicenter Retrospective Study - Wu, Qiuji; Li, Qiu; Zhang, Jun; Luo, Zhumei; Zhou, Jin; Chen, Jing; Luo, Yong (Frontiers in Pharmacology, 2021)
Purpose: Evaluate the cost-effectiveness of PEGylated recombinant human granulocyte-stimulating factor(PEG-rhG-CSF) as a means of achieving primary and secondary prophylaxis against chemotherapy-induced neutropenia cancer cases. Methods: Individuals that underwent PEG-rhG-CSF therapeutics were monitored for 12 months, together with thorough examination of individual medical records for extracting medical-care costings. Both prophylaxis-based therapeutic options (primary/secondary) were scrutinized for cost effectiveness, using a decision-making analysis model derived the perspective of Chinese payers. One-way and probabilistic sensitivity analysis were used to assess the robustness of the model. Results: In summary, 130 clinical cases treated using PEG-rhG-CSF prophylaxis were included in this study: 51 within the primary-prophylaxis (PP) group and 79 within the secondary-prophylaxis (SP) group. Compared with SP, PP-based PEG-rhG-CSF successfully contributed to a 14.3% reduction in febrile neutropenia. In general, PP was estimated to reduce costs by $4,701.81 in comparison to SP, with a gain of 0.02 quality-adjusted life years (QALYs). Equivalent results were found in differing febrile neutropenia(FN) risk subgroups. Sensitivity analyses found the model outputs to be most affected for the average time of hospitalization and for the cost of FN. Conclusion: From the perspective of Chinese payers, PP with PEG-rhG-CSF should be considered cost-effective compared to SP strategies in patients who received chemotherapy regimens with a middle-high risk of FN.